A pH‐Responsive Cluster Metal–Organic Framework Nanoparticle for Enhanced Tumor Accumulation and Antitumor Effect (Adv. Mater. 42/2022). Issue 42 (20th October 2022) - Cheng, Ruoyu; Jiang, Lingxi; Gao, Han; Liu, Zehua; Mäkilä, Ermei; Wang, Shiqi; Saiding, Qimanguli; Xiang, Lei; Tang, Xiaomei; Shi, Minmin; Liu, Jia; Pang, Libin; et al.
Abstract : Tumor Therapy A pH‐responsive cluster metal–organic framework nanoparticle is developed by Wenguo Cui, Baiyong Shen, Hélder A. Santos, and co‐workers in article number 2203915, based on acid‐induced conversion from hydrophilicity to hydrophobicity, leading to aggregated nanoparticles. These nanoparticles inhibit tumor growth and reactivate the tumor microenvironment in both pancreatic and breast cancer models.